2014
DOI: 10.1208/s12249-014-0100-4
|View full text |Cite
|
Sign up to set email alerts
|

Novel Dexamethasone-Loaded Nanomicelles for the Intermediate and Posterior Segment Uveitis

Abstract: Abstract. Development and characterization of dexamethasone (DEX)-encapsulated polymeric nanomicelles have been reported. A low molecular weight di-block copolymer was synthesized and characterized for its structure, molecular weights, critical micelle concentration (CMC), and cytotoxicity in ocular cells. In order to delineate the effects of drug-polymer interactions on drug solubilization in micelle core, a response surface methodology was generated with the help of SAS 9.02 (exploratory model). The method f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…Transscleral permeability studies in excised rabbit sclera indicated a 2.5-fold increase in permeability of DEX with nanomicelles in comaprison to a DEX suspension. This study inidicated the potential of polymeric micelles in improving the bioavailability of DEX in the uvea following topical administration [128]. …”
Section: Pre-clinical Development In-vitro and Biodistribution Stmentioning
confidence: 99%
“…Transscleral permeability studies in excised rabbit sclera indicated a 2.5-fold increase in permeability of DEX with nanomicelles in comaprison to a DEX suspension. This study inidicated the potential of polymeric micelles in improving the bioavailability of DEX in the uvea following topical administration [128]. …”
Section: Pre-clinical Development In-vitro and Biodistribution Stmentioning
confidence: 99%
“…Amphiphilic block copolymers, which possess a hydrophilic head and a hydrophobic tail, selfassemble into micelles in aqueous solution, and the hydrophobic center is achieved in this process. 3,9 These could not only be used as the delivery material of hydrophobic drugs 10 but could also be used in the delivery of hydrophilic drugs 11,12 and peptides, 13 which significantly enhance the permeability of various drugs and prolong retention.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 This low penetration after topical application is primarily because drug entry into the ocular globe is restricted predominantly by corneal barrier functions, which serve to protect the anterior ocular segment, and by the conjunctival-scleral barrier, which 6028 li et al serves to protect the intermediate and posterior segments. 7,8 The anterior corneal barrier is composed of epithelial tight junctions and possesses unique physicochemical properties that involves the opposite characteristics of lipophilic epithelium and hydrophilic stroma. 9 The epithelium and the stroma present different physicochemical properties, and the movement of hydrophilic compounds is limited to the epithelium, whereas the movement of lipophilic compounds is limited to the stroma.…”
Section: Introductionmentioning
confidence: 99%
“…29,36 At present, there are numerous reports discussing the ocular penetration of drugs. 8,9,18,37 To the best of our knowledge, this novel biometry method was used for the first time in vivo to clearly visualize the penetration behaviors of drugs into the corneas of BALB/c mice.…”
mentioning
confidence: 99%